Forest‐Type‐Dependent Water Use Efficiency Trends Across the Northern Hemisphere - Mengjie Wang; Yunhao Chen; Xiuchen Wu; Yan Bai (Geophysical Research Letters)
Abstract Changing climate and increasing atmospheric CO2 significantly regulate forest water use efficiency (WUE). However, magnitudes of the WUE trends and underlying processes driving these patterns in two major forest types, deciduous broadleaf forests (DBFs) and evergreen needleleaf forests (ENFs), across the Northern Hemisphere remain poorly understood. We investigated the WUE trends over the past two decades using eddy covariance observations from 26 forest sites from the FLUXNET2015 data set. Our analyses revealed a greater increase in WUE in DBFs than that in ENFs. The decreased stomatal conductance (Gs) mostly contributed to the increase in WUE in the DBFs, whereas the increased gross ecosystem productivity acted as the main trigger for the increase in WUE in the ENFs. The vapor pressure deficit substantially increased in the DBFs, triggering the decrease in Gs. In contrast, the slight CO2 fertilization and the limited stomatal constraint contributed to the increased gross ecosystem productivity in the ENFs.